2021
DOI: 10.1080/21655979.2021.1884396
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-487a-3p inhibits the growth and invasiveness of oral squamous cell carcinoma by targeting PPM1A

Abstract: Oral squamous cell carcinoma (OSCC) forms the majority of the entire cancerous tumors which occur in the mouth. Current treatment advances, such as surgical resection, chemotherapy, and radiotherapy, have significantly helped reduce OSCC. However, the overall patient survival rate remains relatively low. MiRNAs, a non-coding RNA group, are essential for multiple biological functions, which are essential for the progression of cancer, including survival of the cell, migration, multiplication, differentiation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…It can control TGF-beta/Smad19-21 and mitogen-activated protein kinase22 cellular signaling channels, and proliferating, invading, and 5 Disease Markers migrating processes of cells [42,43]. In OSCC, PPM1A has been reported to be highly expressed and promoted the proliferation and metastasis of OSCC cells, whereas how PPM1A controls the mentioned activities requires in-depth studies [40]. In this study, we found PPM1A may be a target of miR-487a-3p.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…It can control TGF-beta/Smad19-21 and mitogen-activated protein kinase22 cellular signaling channels, and proliferating, invading, and 5 Disease Markers migrating processes of cells [42,43]. In OSCC, PPM1A has been reported to be highly expressed and promoted the proliferation and metastasis of OSCC cells, whereas how PPM1A controls the mentioned activities requires in-depth studies [40]. In this study, we found PPM1A may be a target of miR-487a-3p.…”
Section: Discussionmentioning
confidence: 66%
“…Previously, miR-487a-3p has been reported to be overexpressed in several tumors, such as colon cancer and gastric cancer [38,39]. Importantly, in OSCC, miR-487a-3p was found to display an upregulated level and suppress the proliferation and metastasis of OSCC cells [40]. These findings suggested TSPEAR-AS2 may display its oncogenic roles via sponging miR-487a-3p.…”
Section: Discussionmentioning
confidence: 84%
“…LncRNAs are noncoding RNAs with length longer than 200 nucleotides [3]. The sponge effect of LncRNA on microRNA (miRNA) which participates in OSCC survival [4][5][6], is one of the important mechanisms of the two interactions. Some studies have demonstrated that lncRNA can regulate miRNA aggregation and biological function as competitive endogenous RNA (ceRNA) [7].…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs, 22 nucleotides in length, are a large group of small non-coding RNAs that can exert crucial biological functions by binding to the three prime untranslated region (3 UTR) of their target genes [16,17]. Recently, many miRNAs have been shown to participate in OSCC progression by targeting the genes, including miR-579 [18], miR-487a-3p [19], and miR-210-3p [15]. miR-545-3p, a member of the miRNA family, exerts an inhibitory function in multiple cancers [20][21][22].…”
Section: Introductionmentioning
confidence: 99%